2017
DOI: 10.1038/s41598-017-08950-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rho-GTPases and actin polymerization during Macrophage Tunneling Nanotube Biogenesis

Abstract: Macrophage interactions with other cells, either locally or at distances, are imperative in both normal and pathological conditions. While soluble means of communication can transmit signals between different cells, it does not account for all long distance macrophage interactions. Recently described tunneling nanotubes (TNTs) are membranous channels that connect cells together and allow for transfer of signals, vesicles, and organelles. However, very little is known about the mechanism by which these structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 64 publications
(113 reference statements)
4
130
2
Order By: Relevance
“…In contrast, TNTs that also form by extending long protrusions remain stable structures that connect two cells. Furthermore, while TNTs have been reported to form in short 4-hour cultures of RAW/LR5 macrophages (Hanna et al, 2017), fusion of peritoneal macrophages begins 9 hours after addition of IL-4 (Faust et al, 2017). Finally, as revealed in our studies, short rather than long protrusions predominantly initiate macrophage fusion.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, TNTs that also form by extending long protrusions remain stable structures that connect two cells. Furthermore, while TNTs have been reported to form in short 4-hour cultures of RAW/LR5 macrophages (Hanna et al, 2017), fusion of peritoneal macrophages begins 9 hours after addition of IL-4 (Faust et al, 2017). Finally, as revealed in our studies, short rather than long protrusions predominantly initiate macrophage fusion.…”
Section: Discussionsupporting
confidence: 63%
“…TNTs are thin long membranous tubes with diameters of 50-800 nm connecting two cells that have been reported in numerous cell types, including macrophages (Rustom et al, 2004;Kimura et al, 2012;Onfelt et al, 2006;Hanna et al, 2017). Formation of TNTs requires F-actin and, as recently shown in macrophages, depends on the activity of Rac1, Cdc42 and WASp (Hanna et al, 2017). Despite the general requirement for F-actin and the activators of actin polymerization, there seems to be clear distinctions between TNTs and fusion-competent protrusions.…”
Section: Discussionmentioning
confidence: 93%
“…Not surprisingly, cytoskeleton regulators, such as N-WASP, Rac1, ezrin and Cdc42, have been linked to TNTs (Arkwright et al, 2010;Hanna et al, 2017;Hase et al, 2009;Lachambre et al, 2014). However, and despite structural similarities, a recent study revealed that TNT formation and TNT-mediated vesicle transfer is negatively regulated by the filopodia-promoting complex Cdc42-IRSp53-VASP (IRSp53 is also known as BAIAP2), suggesting that the formation of filopodia and TNTs involves different mechanisms that may depend on the cell or stimulus (Delage et al, 2016).…”
Section: The Role Of Cx43 Hemichannels In Paracrine Communicationmentioning
confidence: 99%
“…In addition, the role of CDC42 and Rho-GTPases in TNT formation is not fully investigated. A report of Hanna et al, (2017), demonstrated that the activity of CDC42 and Rho-GTPases positively contributes to the formation of TNTs in macrophages. In contrast, Delage et al, (2016); found that CDC42/IRSp53/VASP negatively regulates the formation of TNTs.…”
Section: Oaβ Propagation To Healthy Cells Is Mediated By Transport Inmentioning
confidence: 99%
“…Some of these studies also reveal that vesicle transfer, recycling vesicles, lysosomes and molecule involved in membrane expansion play a role in the formation of TNTs, the actin membrane protrusions (Bhat et al, 2018;Victoria and Zurzolo, 2017;Hase et al, 2009). Actin depolymerization and actin modulations have been shown to inhibit the formation of these structures (Hanna et al, 2017).…”
mentioning
confidence: 99%